2016
DOI: 10.2350/15-05-1638-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Molecular Testing in the Diagnosis and Management of Children with Thyroid Lesions

Abstract: Thyroid nodules occur in 1-2% of children, and identifying which nodules are malignant is often challenging. Cytologic evaluation facilitates the diagnosis of thyroid lesions (TLs), but in 10-40% of cases the interpretation is indeterminate. Patients with indeterminate diagnoses are often treated with hemithyroidectomy followed by completion thyroidectomy, if cancer is found in the initial specimen. Exposing patients to multiple surgeries increases costs and morbidity. The American Thyroid Association states t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 26 publications
2
58
1
Order By: Relevance
“…TERT promoter mutation appears to also be uncommon in pediatric thyroid cancers as suggested by the study of Ballester et al, which found no TERT promoter mutation in 27 pediatric thyroid cancers, including 25 PTC, 1 FTC and 1 MTC (Ballester et al 2015). Larger studies on pediatric thyroid cancer, however, are needed to confirm this finding.…”
Section: Common Occurrence Of Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…TERT promoter mutation appears to also be uncommon in pediatric thyroid cancers as suggested by the study of Ballester et al, which found no TERT promoter mutation in 27 pediatric thyroid cancers, including 25 PTC, 1 FTC and 1 MTC (Ballester et al 2015). Larger studies on pediatric thyroid cancer, however, are needed to confirm this finding.…”
Section: Common Occurrence Of Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 91%
“…We included all the studies on TERT promoter mutations in thyroid cancer published in English in Pubmed as of November 2015 with identifiable information on thyroid tumor types. The pooled analyses included nonselective cases from different studies available for the analyzed parameters as presented in the corresponding tables and figures and did not include four studies which were each focused on highly selective special cases, including pediatric thyroid cancer (Ballester et al 2015), papillary thyroid microcarcinomas (de Biase et al 2015), advanced tall-cell PTC only (Dettmer et al 2015), and distant-metastasis PTC only (Gandolfi et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal rearrangement is more common than point mutation in pediatric PTC (53 vs. 33%)3. ETV6 - NTRK3 fusions are present in 18% and associated with unfavorable histology such as solid, insular, or trabecular patternsBallester et al [15]PTC25 (age range, 10–19 years)FNAFFPE tissueIon torrent PGMAmpliSeq Cancer Hotspot Panel v2 (50 genes)Torrent Suit version 4.2No additional mutation detected by NGS in cases lacking mutations in BRAF, RET/PTC, TERT promoter mutation at initial analysisLanda et al [28]PDC34Fresh frozen tissue ( N  = 37)FFPE tissue ( N  = 80)N/AMSK-IMPACT cancer exome panel (341 genes)MSK-IMPACT pipeline1. Mutation number is greater in AC (6 ± 5) than PDC (2 ± 3), and predominantly affected genes are TP53 , TERT promoter, PI3K/AKT/mTOR pathway effector, SWI/SNF subunit, and histone methyltransferase2.…”
Section: Ngs Application In the Diagnosis Of Indeterminate Cytologymentioning
confidence: 99%
“…(3) ETV6 - NTRK3 fusion was identified in 18% of samples, and was associated with aggressive histologic features such as non-encapsulation, solid/insular/trabecular patterns, extensive glandular involvement, and thick tumor fibrosis [14]. Ballester et al analyzed FFPE and FNA samples from 25 pediatric PTCs (age range 10–19 years, median 14 years) using the 50-gene Ion AmpliSeq Cancer Hotspot Panel v2 on the Ion Torrent PGM sequencer [15]. No additional mutations were detected using the NGS assay on pediatric PTCs that initially were negative for BRAF V600E mutation, RET/PTC1/3 fusion, and TERT promoter mutation [15].…”
Section: Genetic Alteration Of Thyroid Cancer and Ngsmentioning
confidence: 99%
See 1 more Smart Citation